Cambodia : 2010 Article IV Consultation-Staff Report; Staff Statement and Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Cambodia. (IMF Staff Country Reports; Country Report ;, 2011)
Prior to the global crisis, Cambodia enjoyed a decade of high growth and relative stability. However, as a result of the global crisis, output collapsed, and longstanding structural vulnerabilities have been exposed. Discussions focused on the dual policy challenge to safeguard macroeconomic stability and policy credibility, and to lay the foundations for broader-based and inclusive growth. It is recommended that the next Article IV Consultation take place on the standard 12-month cycle. IMF staff underscored the need for better and faster data for key economic statistics.